Valuation of the economic impact of air pollution to promote public welfare in Jakarta - Susilo, Y Sri; Herawan, Jonathan; Parningotan, Firman (Department of Accounting, Faculty of Business, Universitas PGRI Yogyakarta, 2024)
This research aims to conduct a valuation analysis of the economic impact of air pollution that occurs in DKI Jakarta Province. By using mapping from satellite imagery and the 2016 Input-Output table which was iterated using the RAS Partial Survey method to become the 2023 Input-Output table. From the results of research that uses the impact (shock) of the implementation of the weak complimentary which is reflected through the environmental adjustment tax (EAT) The results showed that air pollution in DKI Jakarta Province contributed negatively to the economy amounting to IDR 8,981,659,208,407,380.00. Based on the results of the income and output multiplier analysis, various results were obtained, but the extractive sector was better able to operate without weak complimentary and the results of linkage and mapping proved that the Wholesale and Retail Trade sectors; Car and Motorcycle Repair; Transportation and Warehousing; and Government Administration, Defense and Social Security must contribute maximally to air pollution in West Jakarta, Central Jakarta, North Jakarta and South Jakarta. The recommendation from this research is the need for policy synergy between the DKI Jakarta Provincial Government, the business world, academics, media and community leaders by creating a 3P (People, Planet, Profit) Jakarta Plan to solve pollution and environmental problems in DKI Jakarta Province